2021
DOI: 10.1186/s13024-021-00477-w
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type FUS corrects ALS-like disease induced by cytoplasmic mutant FUS through autoregulation

Abstract: Mutations in FUS, an RNA-binding protein involved in multiple steps of RNA metabolism, are associated with the most severe forms of amyotrophic lateral sclerosis (ALS). Accumulation of cytoplasmic FUS is likely to be a major culprit in the toxicity of FUS mutations. Thus, preventing cytoplasmic mislocalization of the FUS protein may represent a valuable therapeutic strategy. FUS binds to its own pre-mRNA creating an autoregulatory loop efficiently buffering FUS excess through multiple proposed mechanisms inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…The homeostasis of FUS protein levels is controlled by autoregulatory mechanisms involving the retention of intron 6 and 7 [ 33 , 81 ]. Furthermore, mutations in the NLS domain lead to the reduction of FUS exon 6 and 6 repression, contributing to FUS abnormal cytoplasmic accumulation [ 33 , 81 ]. Using RT-PCR, we calculated the percentage of intron 6/7 retention in mutant FUS OPCs and their isogenic controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homeostasis of FUS protein levels is controlled by autoregulatory mechanisms involving the retention of intron 6 and 7 [ 33 , 81 ]. Furthermore, mutations in the NLS domain lead to the reduction of FUS exon 6 and 6 repression, contributing to FUS abnormal cytoplasmic accumulation [ 33 , 81 ]. Using RT-PCR, we calculated the percentage of intron 6/7 retention in mutant FUS OPCs and their isogenic controls.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that FUS mislocalizes in the cytoplasm of mutant OPCs, consistent with previous reports on oligodendrocytes in FUS mouse model and FUS -ALS patients [ 58 , 82 , 90 ]. Recent studies found that mutant FUS autoregulatory mechanisms are altered and contribute to its cytoplasmic accumulation [ 33 , 81 ]. Consistent with the immunofluorescence data, a significant decrease in intron 6 and 7 retention was identified in OPCs with FUS NLS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…RBPs, including FUS, can selectively bind to specific RNAs and transport them into sEVs [ 16 , 19 ]. FUS, a highly conserved protein, was initially identified as a fusion oncogene in human liposarcomas [ 37 ] and has been shown to play a critical role in normal central nervous system development and neuron survival [ 38 , 39 ]. FUS mutations have been linked to neurodegenerative disorders, such as ALS and frontotemporal dementia (FTD) [ 40 , 41 ], making FUS a key target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequences are provided in Table S2. For FUS autoregulation, primer sequences were used as described previously 27 …”
Section: Methodsmentioning
confidence: 99%